Inadequate pain relief in ambulatory patients with human immunodeficiency virus disease in Port Harcourt - Ebirim LN (Dove Medical Press, 2013)
Longinus Ndubuisi Ebirim, Job Gogo Otokwala Department of Anaesthesiology, University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria Objectives: To estimate the prevalence of pain in ambulatory patients with human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) in Port Harcourt and to determine the type, site, severity, and adequacy of the treatment of pain in these patients. Materials and methods: A cross-sectional survey was carried out at two antiretroviral therapy centers in Port Harcourt, Nigeria. A data sheet, the brief pain inventory, and the short form of the McGill pain questionnaire were used and 157 patients in various stages of HIV/AIDS participated in the study. Results: About 83.7% (129/157) of the ambulatory patients with HIV/AIDS complained of pains. Of the patients who reported pain 61.24% (79/129) reported nociceptive pain while 38.76% (50/129) reported neuropathic pain. Chest pain was the most frequent site of pain followed by headache. About 82% (106/129) of those who complained of pain received some form of analgesic, but only 23.58% (25/106) of these obtained adequate pain relief. The majority of the participants had significant impairment of their quality of life due to the severity of their pain. Conclusion: Pain associated with significant impairment of quality of life is common in ambulatory patients with HIV/AIDS in Port Harcourt. Whereas the majority of the patients used various pain relief methods, analgesia was inadequate. Keywords: ambulatory HIV/AIDS patients, pain, inadequate relief